2005
DOI: 10.1128/mcb.25.11.4552-4564.2005
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo HP1 Targeting Causes Large-Scale Chromatin Condensation and Enhanced Histone Lysine Methylation

Abstract: Changes in chromatin structure are a key aspect in the epigenetic regulation of gene expression. We have used a lac operator array system to visualize by light microscopy the effect of heterochromatin protein 1 (HP1) ␣ (HP1␣) and HP1␤ on large-scale chromatin structure in living mammalian cells. The structure of HP1, containing a chromodomain, a chromoshadow domain, and a hinge domain, allows it to bind to a variety of proteins. In vivo targeting of an enhanced green fluorescent protein-tagged HP1-lac represso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
152
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(159 citation statements)
references
References 56 publications
5
152
0
1
Order By: Relevance
“…In support of the idea that citrullinated histone affects the chromatin structure in patients, we also found that HP1-␣, a protein that has an important role in chromatin compaction (Verschure et al, 2005), was decreased in NAWM from MS tissue. Although the effects of these changes on differentiation are not known, it has been shown that changes in the acetylation state of histones affect the ability of oligodendrocyte progenitors to differentiate into myelinating cells both in vitro and in vivo (Marin-Husstege et al, 2002;Shen et al, 2005).…”
Section: Discussionsupporting
confidence: 65%
“…In support of the idea that citrullinated histone affects the chromatin structure in patients, we also found that HP1-␣, a protein that has an important role in chromatin compaction (Verschure et al, 2005), was decreased in NAWM from MS tissue. Although the effects of these changes on differentiation are not known, it has been shown that changes in the acetylation state of histones affect the ability of oligodendrocyte progenitors to differentiate into myelinating cells both in vitro and in vivo (Marin-Husstege et al, 2002;Shen et al, 2005).…”
Section: Discussionsupporting
confidence: 65%
“…In these lines, expression of fused proteins carrying the lacI-DNA-binding domain results in their targeting to the reporter gene. Previous studies showed that, in general, targeting HP1 proteins to a reporter gene induces silencing (Ayyanathan et al 2003;Li et al 2003;Verschure et al 2005;Smallwood et al 2007). Actually, in line S9.2, expression of HP1a-lacI results in silencing of the reporter gene, which is stronger in males (Fig.…”
Section: Hp1c Localizes To Active Chromatin Domainsmentioning
confidence: 99%
“…H3K9me3 provides a binding site for heterochromatin protein 1 (HP1), a family of non-histone chromatin proteins found in different isoforms from Schizosaccharomyces pombe to human. HP1 proteins induce formation of heterochromatin when artificially targeted to heterologous sites within the genome (3), an effect that is concomitant with induction of local H3K9me3 (4). Given the important roles of heterochromatin in gene regulation, it is surprising that mammalian HP1␤ is the only HP1 protein essential for viability (5).…”
mentioning
confidence: 99%